Vibration Reduction of Juicer: A Case Study. (September 2015) - Parey, Anand
Juicers are one of the most common kitchen appliances. A renowned company in this field experienced high vibration level in one of the model which was under development. High vibrations are unacceptable as they lead to early failure of the component. The product was about to launch and vibration levels needed to be below the acceptable limits without any changes in design of the model. This paper presents a case study on reduction of vibration level of juicer using two methods, firstly, by using tuned mass damper and secondly by modifying the shape of isolators. The vibration level came down below the acceptable limits by using modified isolator.